2015
DOI: 10.3906/sag-1406-71
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patency following revision technique ofhigh-velocity arteriovenous fistula

Abstract: to 70) years] subsequently developed steal syndrome. These patients were treated with arterial pressure-controlled polytetrafluoroethylene banding or constriction with polypropylene suturing technique. Patients were followed in the outpatient clinic at regular intervals.Results: Symptoms were not relieved during the first 15 days in 4 patients; therefore, reintervention was performed. Thrombosis occurred in one patient after reintervention. No early or late complications were detected in other patients, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Accordingly, literature recommended surgery only for severe cases (grade ⩾2). 12,13 Among the others, vein outflow binding has been largely described as an appealing alternative considering its benign nature: the procedure can be performed under local anesthesia, and it is minimally invasive preserving the effectiveness of two-needle hemodialysis. 14 However, several authors have reported high rates of failure and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, literature recommended surgery only for severe cases (grade ⩾2). 12,13 Among the others, vein outflow binding has been largely described as an appealing alternative considering its benign nature: the procedure can be performed under local anesthesia, and it is minimally invasive preserving the effectiveness of two-needle hemodialysis. 14 However, several authors have reported high rates of failure and thrombosis.…”
Section: Discussionmentioning
confidence: 99%